Modulation of intracellular pH in human ovarian cancer. - Sanhueza, C.; Araos, J.; Naranjo, L.; Villalobos, R.; Westermeier, F.; Salomon, C.; Beltrán, A.R.; Ramírez, M.A.; Gutiérrez, J.; Pardo, F.; Leiva, A.; Sobrevia, L. (Current Molecular Medicine, 2016)
To sustain tumor growth, the cancer cells need to adapt to low levels of oxygen (i.e., hypoxia) in the tumor tissue and to the tumor-associated acidic microenvironment. In this phenomenon, the activation of the sodium/proton exchanger 1 (NHE1) at the plasma membrane and the hypoxia-inducible factor (HIF) are critical for the control of the intracellular pH (pHi) and for hypoxia adaptation, respectively. Interestingly, both of these mechanisms end in sustaining cancer cell proliferation. However, regulatory mechanisms of pHi in human ovary tissue and in malignant ascites are unknown. Additionally, a potential role of NHE1 in the modulation of H+ efflux in human ovarian cancer cells is unknown. In this review, we discussed the characteristics of tumor microenvironment of primary human ovarian tumors and tumor ascites, in terms of pHi regulatory mechanisms and oxygen level. The findings described in the literature suggest that NHE1 may likely play a role in pHi regulation and cell proliferation in human ovarian cancer, potentially involving HIF2α activation. Since ovarian cancer is the fifth cause of prevalence of women cancer in Chile and is usually of late diagnosis, i.e., when the disease jeopardizes peritoneal cavity and other organs, resulting in reduced patient survival, new efforts are required to improve patient–life span and for a better understanding of the pathophysiology of the disease. The potential advantage of the use of amiloride and amiloride–derivatives for cancer treatment in terms of NHE1 expression and activity is also discussed as a therapeutic approach in human ovarian cancer.
Keywords: intracellular pH